Breaking the locomotive of History is an action against the program of the apparatus: : notes on the critique of technique in Benjamin and Flusser. - Del Lama, Fernando Araújo (2019)
We intend to establish a critical-comparative examination between the reflections of Walter Benjamin and of Vilém Flusser on technique. The aim of this investigation consists in bringing both thinkers closer, keeping their idiosyncratic traits, through a critique of technique that unfolds on the horizon of the exile experience provoked by the Nazi-fascist rise and which expresses itself as a redirection of the inherent potentials of technique for human emancipation (Benjamin) or as resistance against the logic of codes and programs (Flusser).